Pharmacokinetic interactions of esaxerenone with amlodipine and digoxin in healthy Japanese subjects - Yoshiaki Kirigaya (BMC Pharmacology and Toxicology, 2020)
Abstract Background To investigate the effects of coadministration of esaxerenone with amlodipine on the pharmacokinetics (PK) of each drug, and of esaxerenone on the PK of digoxin. Methods In three open-label, single-sequence, crossover studies, healthy Japanese males received single oral doses of esaxerenone 2.5 mg (Days 1, 15), with amlodipine 10 mg/day (Days 8–18) (Study 1, N = 24); single doses of amlodipine 2.5 mg (Days 1, 21), with esaxerenone 5 mg/day (Days 8–25) (Study 2; N = 20); or digoxin 0.25 mg/day (Days 1–15) with esaxerenone 5 mg/day (Days 11–15) (Study 3; N = 20). PK parameters and safety were assessed. Results Study 1: esaxerenone peak plasma concentration (Cmax) and time to Cmax were unaltered by amlodipine coadministration, but mean half-life was slightly prolonged from 18.5 to 20.9 h. Geometric least-squares mean (GLSM) ratios for Cmax, area under the plasma concentration–time curve (AUC) from zero to last measurable concentration and from zero to infinity for esaxerenone + amlodipine versus esaxerenone were 0.958, 1.154, and 1.173, respectively. Study 2: corresponding GLSM ratios for amlodipine + esaxerenone versus amlodipine were 1.099, 1.185, and 1.214. Study 3: esaxerenone did not markedly alter digoxin PK. GLSM ratios for Cmax, trough plasma concentration, and AUC during a dosing interval for digoxin versus esaxerenone + digoxin were 1.130, 1.088, and 1.072, respectively. Conclusions No drug–drug interactions are expected during combination therapy with esaxerenone and either amlodipine or digoxin, based on a lack of any clinically relevant PK changes. Trial registration Studies 1 and 2: JapicCTI-163379 (registered on 20 September 2016); Study 3: JapicCTI-163443 (registered on 24 November 2016).